2016
DOI: 10.1111/ped.13073
|View full text |Cite
|
Sign up to set email alerts
|

Serum oxidative stress parameters and paraoxonase‐1 in children and adolescents exposed to passive smoking

Abstract: Secondhand smoke exposure is associated with increased oxidative stress and decreased paraoxonase-1 without any change in antioxidant status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
(71 reference statements)
1
8
0
Order By: Relevance
“…Kahraman et al also observed a similar result in their study comprised of 80 children (40 exposed, 40 not exposed, aged 5-17 years). They found that total oxidant status and oxidative stress index were increased in children exposed to secondhand smoke; however, total antioxidant status was similar in both groups [36]. In the light of our results and the literature on this topic, it may be feasible to suggest that passive smoking initially effects oxidant levels, but not antioxidant levels.…”
Section: Discussionsupporting
confidence: 38%
“…Kahraman et al also observed a similar result in their study comprised of 80 children (40 exposed, 40 not exposed, aged 5-17 years). They found that total oxidant status and oxidative stress index were increased in children exposed to secondhand smoke; however, total antioxidant status was similar in both groups [36]. In the light of our results and the literature on this topic, it may be feasible to suggest that passive smoking initially effects oxidant levels, but not antioxidant levels.…”
Section: Discussionsupporting
confidence: 38%
“…Inflammation and oxidative stress (OS) are often considered as pre-pathological conditions originated from numerous non-optimal environments and working circumstances [1], from modifiable habits (e.g., tobacco smoking) [2,3] and from several health impairments which may represent both their cause and effect [4]. Various risk factors are able to induce redox imbalance in humans, and among these, adiposity [5,6] and second hand smoke (SHS) may play an important role in OS induction, in particular in youths [7,8,9]. Indeed, excessive adipose tissue and high exposure to SHS may induce a dysregulation of the balance between oxidants and antioxidants in favor of the oxidants [10,11], leading to OS [12], which determines a condition that often precedes the onset of several diseases [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We found that PON1 rs662 T allele might decrease the risk of EGJA in ever smoking subgroup, suggesting that PON1 rs662 C>T polymorphism might act as a protective factor for EGJA. Kahraman et al found tobacco exposure increased oxidative stress and decreased paraoxonase-1 [ 33 ]. The coding region PON1 rs662 C>T polymorphism (R192Q) leads to an amino acid substitution and determines a substrate dependent effect on activity.…”
Section: Discussionmentioning
confidence: 99%